2010
DOI: 10.1186/1748-5908-5-23
|View full text |Cite
|
Sign up to set email alerts
|

Part I, Patient perspective: activating patients to engage their providers in the use of evidence-based medicine: a qualitative evaluation of the VA Project to Implement Diuretics (VAPID)

Abstract: BackgroundThis qualitative evaluation follows a randomized-control trial of a patient activation intervention in which hypertensive patients received a letter in the mail asking them to discuss thiazide diuretics with their provider. Results of the parent study indicated that the intervention was effective at facilitating discussions between patients and providers and enhancing thiazide prescribing rates. In the research presented here, our objective was to interview patients to determine their receptivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…In prior work, veterans expressed concern over cost burdens to VHA, suggesting a sense of "stewardship" of limited resources. [21][22][23] This may reflect the unique place veterans have in society, having served in the military and now being recipients of a promised benefit. Ultimately, fee-basis care has been used to improve access, but unlimited fee-basis care would turn VHA into an insurance benefit and not the integrated healthcare system it is currently.…”
Section: Discussionmentioning
confidence: 97%
“…In prior work, veterans expressed concern over cost burdens to VHA, suggesting a sense of "stewardship" of limited resources. [21][22][23] This may reflect the unique place veterans have in society, having served in the military and now being recipients of a promised benefit. Ultimately, fee-basis care has been used to improve access, but unlimited fee-basis care would turn VHA into an insurance benefit and not the integrated healthcare system it is currently.…”
Section: Discussionmentioning
confidence: 97%
“…Patient activation “emphasizes patients’ willingness and ability to take independent actions” [30] by understanding their “role in the care process and having the knowledge, skill, and confidence to manage one’s health and health care” [31]. In general, strong evidence exists across a variety of diseases and conditions other than osteoporosis that higher patient activation levels predict healthy behaviors and are associated with better health outcomes and care experiences, with lesser evidence of reductions in health care costs [29, 30, 32–36]. Strong evidence also shows that well-crafted interventions that tailor the intervention to each patient lead to clinically significant improvements in patient activation levels and often result in improved health outcomes [30, 32, 37].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that patients may play an important part in promoting evidence-based practice important for patient safety but also for quality of care [1921]. Studies also suggest that patients who are more informed are more involved, experience less decisional conflict, and choose less invasive treatments [16].…”
Section: Introductionmentioning
confidence: 99%